Deciding to Decide: How Decisions Are Made and How Some Forces Affect the Process. Issue 1 (January 2016) - McConnell, Charles R.
Abstract : There is a decision-making pattern that applies in all situations, large or small, although in small decisions, the steps are not especially evident. The steps are gathering information, analyzing information and creating alternatives, selecting and implementing an alternative, and following up on implementation. The amount of effort applied in any decision situation should be consistent with the potential consequences of the decision. Essentially, all decisions are subject to certain limitations or constraints, forces, or circumstances that limit one's range of choices. Follow-up on implementation is the phase of decision making most often neglected, yet it is frequently the phase that determines success or failure. Risk and uncertainty are always present in a decision situation, and the application of human judgment is always necessary. In addition, there are often emotional forces at work that can at times unwittingly steer one away from that which is best or most workable under the circumstances and toward a suboptimal result based largely on the desires of the decision maker.